EFEK APLIKASI KOMPOS SAMPAH DAN KOTORAN KAMBING TERHADAP SERAPAN UNSUR HARA KALIUM DAN HASIL TANAMAN BAWANG MERAH PADA TANAH TERDAMPAK ERUPSI GUNUNG KELUD - Bagas Septya Pradana; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The soil containing volcanic ash from Mount Kelud was contain nutrients in the form that was not available for the soil, so that the soil diffficult to process. One of the efforts to solve that is by organic matter application that can improve availability of nutrient in the soil and improve plant growth. The purpose of this study was to evaluate the effect of compost application on potassium uptake, and yield of onion on Mount Kelud eruption-impacted soil. This study used a randomized block design with five treatments and three replications. The treatments tested were K0 = 100% inorganic fertilizer; K1= 100% goat manure compost; K2= 100% garbage compost; K3= 50% inorganic fertilizer + 50% goat manure compost; and K4= 50% inorganic fertilizer + 50% garbage compost. The results showed that application of waste compost and goat manure compost significantly affected sodium uptake, but it did not significantly affect potassium uptake compared to inorganic fertilizer application. Furthermore, application of waste compost and goat manure compost significantly affected plant heightÂ and number of leaves, but it did not significantly affect number of tillers, number of bulbs, diametre of bulbs, fresh weight of bulbs and dry weight of bulbs of red onion plant, compared to inorganic fertilizer application. Application of 20 t goat manure compost ha-1 gave the highest number of leaves (67), and plant height (49.77 cm).